A love blessed by God: narratives in the popular Islamic novels of Malaysia - Abdul Rani, Mohd Zariat (Center for Southeast Asian Studies, Hankuk University of Foreign Studies, 2014)
This article departs from a current development in the Malaysian literary scene, namely the emergence of what is known as the ‘phenomenon of popular Islamic novels.’ The phenomenon is marked by an overwhelming public reception towards novels that outwardly display Islamic characteristics, such as in their titles, cover illustrations, and blurbs. The development is interesting because these bestselling popular Islamic novels were preceded by teenage romance novels which were imbued with erotic nuances. This would indicate a significant shift in the popular literary tastes of Malaysian readers. As such, the present study aims to observe this shift from a critical perspective, by focusing on the content of these popular Islamic novels, so as to identify the themes contained within, as well as the role Islam plays in their construction. To that end, two popular Islamic novels will be analysed, namely Melakar Cinta Firdausi by Nurul Aini K. Azhari and Aimi Nabihah Mohamad (PTS Litera Utama Sdn Bhd, 2009), and Ya Fattah; Cinta Sakti by Noorfadzilah (Buku Prima Sdn Bhd, 2009). The study finds that both novels present romantic themes that are Islamic, that are addressed through the manipulation of narrative devices and the usage of an Islamic moral scheme. The foregrounding of Islamic romantic themes goes against the trend of preceding popular novels that were more inclined towards erotic themes.